Utvärdering av två hanteringstekniker för hundmöten när hunden är kopplad - Almquist, Emma (2017)
Dogs’ lives are shaped by their owners’ lives, they go where the owners want to go and they live where the owners want to live. The day to day interactions between owner and dog, such as during walks, can affect both their relationship and the welfare of the dog. According to Swedish legislation dogs have to be walked and exercised regularly, however, the owners are also demanded to keep their dogs under control. The most common way to control dogs during walks outside is to keep them on a leash. Dog to dog encounters during walks can be problematic. When dogs meet on leash they display more threatening signals towards each other than do dogs off leash. The purpose of this study was to evaluate two management techniques for dog to dog encounters when walking on a leash. This was done by comparing dog behavior between two management techniques/treatments and from those results discuss whether one of the techniques might make the encounter easier to handle for the dog. One treatment was called “secure” (S), where the dogs encountered the other dog with a person characterized as secure, were walked in a curve away from, and placed on the opposite side of the person as the other dog. The other treatment was called “unpredictable/disorganized” (O/D), where the dogs encountered the other dog with a person characterized as unpredictable and disorganized, and were walked straight towards and on the same side of the person as the other dog. This study found two significant differences in behavior between the treatments. The dogs wagged their tail more before and during the encounter in treatment O/D. In treatment S, they held their head higher at the very end of the behavior registrations, after the encounter. In addition to these differences a few tendencies were found. Before and during the meeting in treatment O/D, dogs pulled more in direction towards the other dog, while dogs in treatment S pulled more in the forward direction. The last statement was true also for dogs in treatment S over the entire sampling distance. From these results it was concluded that there were differences in dogs’ behavior between the two management techniques. Dogs seemed to focus more on the other dog in treatment O/D. For dogs that have problems dealing with dog to dog encounters it is probably easier to train these encounters if the person walking the dog is secure, walks in a curve and places the dog on the opposite side of themselves as the other dog. This might be helpful because the dog does not focus as much on the challenging encounter, which might lower stress levels and thus make the dog more susceptible to training.